Identification of Adult Populations at Hiah Risk for Dental - Virginia Powell, DMD; Brian G. Leroux, PhD; Jean A. Martin, DDS, MPH; B. Alexander White, DDS, MS, D (Blackwell Synergy, 2000)
The purpose of this study is to test the usefulness of dental insurance claims history, supplemented with radiographic caries diagnoses, as a means of identifying caries-active and caries-inactive working adults, as determined by bacterial levels. Computerized identification of at-risk groups may facilitate subject selection for clinical trials designed to test caries-preventive strategies